(untitled) (REMUNOM, 2026)
This article explores the diverse functions and manifestations of education throughout history. Libâneo (2014) and Pimenta (2016) emphasize its structure both inside and outside schools, highlighting the need for other educational forms within various institutions and the divergent decision-making systems in educational practices within socio-political contexts. Based on this, Brandão (1989) argues for the importance of the pedagogue’s role in both non-school and school educational environments, fostering reflection on the awareness that socio-political education articulates. Meanwhile, França-Carvalho (2007) mentions the contributions of creating curricula and teaching methods focused on the training of pedagogues and the analysis of their mediation within the contexts in which they are involved in the human, social, and political dimensions. Saviani (2008) emphasizes that governmental measures aimed at Basic Education seek to offer appropriate means and approaches to encourage and promote human development. It is important to highlight that the evolution of society influences the educational process, which is an integral part of public policies. Therefore, this research aims to describe and highlight academic productions in Brazil that are considered socio-political. A bibliographic review is suggested, as Marconi and Lakatos (2002) state; bibliographic research is capable of gathering and organizing previously studied archives, giving them new dimensions and incredible depth. The selection of the study topic is justified by the contribution of education in the socio-political context. Furthermore, by analyzing the studies already carried out, it is possible to identify the main theorists, understand the evolution of public policies, and guide future research, as Severino (2013) assures.